P419 Outcomes for patients with severe acute ulcerative colitis. (25th January 2019) - Shivakumar, M; Grant, R; Lynch, R; Manship, T; Jagger, F; Satsangi, J; Ho, G T; Plevris, N; Lees, C; Arnott, I
Abstract: Background: Acute severe ulcerative colitis (ASUC) usually requires hospitalisation, immediate management and is considered a medical emergency. Historically, the management of ASUC has been with intravenous steroids followed by colectomy in unresponsive patients. Management of ASUC has since evolved with the introduction of rescue therapy as second-line treatment such as cyclosporine and infliximab. Surgical therapy is usually considered if there is no response to medical therapy. The aim of this study was to evaluate the impact of second-line medical therapies and assess whether these had improved patient outcomes. Methods: We assessed patients admitted to a single-centre with acute ulcerative colitis between November 2011 and October 2016. All patients received intravenous steroids as the first-line medical therapy. Patients with previous colectomy or other variants of UC were excluded. Data were collected retrospectively from electronic patient records. Data included demographics, medical and surgical management prior to, during and after admission. Treatment response was defined as discharge from hospital with no further acute medical or surgical treatment. Clinical findings for the first 10 days on admission, such as radiological, haematological and biochemical test results, were collected. Statistical analysis of data included comparisons with χ 2 and Fisher exact test. Results: In total, 362 patients were analysed, the youngest being 3 years old and the oldest 88. A total of 151 of these patients were newly diagnosed with UC. One patient died during admission before receiving second-line treatment. Over the 5-year period, 106 patients received second-line treatment of which 86 received cyclosporine and 20 received biologics. Amongst this group, 65 responded to treatment. Use of biologics did not change over the 5 years, averaging at 4 patients per year. In the first year, 5.1% of patients required colectomy after second-line treatment. This became 4.1%, 1.2%, 1.5% and 4.9% in subsequent years, observing a trend towards improvement. It was observed that some patients were not suitable for second-line treatment and proceeded directly to surgery (3.0%). Conclusions: There seems to be a downward trend of colectomy rates in patients who have received second-line treatment. There was no increase in use of biologics but this may be seen in data from more recent years. Further evaluation on a longer time scale and a larger sample size may provide more information on the evolution of management strategies.